Molecular imaging with 68Ga-PSMA PET/CT in high grade glioma: A biomarker for tumour neo-angiogenesis - Sharjeel Usmani; Khulood Al Riyami; Shah P Numani; Syed Furqan Hashmi; Anjali Jain; Rashid al Sukaiti; Najeeb Ahmed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
There are several promising radiotracers used for both staging and restaging of primary and recurrent brain tumours based on various mechanisms of tracer localization in tumour cells. 68Ga-PSMA PET has extremely low background uptake in normal brain tissue and consequently high tumour-to-brain ratio making it a promising imaging radiotracer for gliomas. 68Ga-PSMA demonstrates utility in evaluating high grade glioma during both initial workup or when suspecting recurrence. Herein the authors evaluate the role of this imaging modality and the potential future it holds in the management of high grade gliomas. Keywords: 68Ga-PSMA; PET/CT; brain tumors; PET/CT; gliomas; Glioblastoma Multiforme